Dune messiah. - Herbert, Frank (New York : Putnam, 1969)
Living in exile on the planet Dune, Paul Atreides finally realizes the destiny for which he had been prepared as the product of numerous genetic experiments.
Sequel to Dune.
Wilson's Fiction.
Wilson's Senior High School.
Young Adult.
Young Adult
Keywords: Dune (Imaginary place) -- Fiction; Science fiction; Science fiction